The Future of Nuclear Security in the Asia-Pacific: Expanding the Role of Southeast Asia - Julius Cesar Trajano; Mely Caballero-Anthony (International Journal of Nuclear Security, 2020)
The nature of regional cooperation on capacity building taking place in Southeast Asia certainly provides a good foundation to pursue a more robust collaborative framework for nuclear security in the wider Asia-Pacific region. A step in this regard is to have a regional action plan/roadmap for nuclear security in the Asia-Pacific that could institutionalize cooperation between Association of Southeast Asian Nations (ASEAN) and other countries in the wider region, fostering closer collaboration. The paper recommends three practical mechanisms to expand cooperation frameworks in Southeast Asia to the broader Asia-Pacific region: (1) strengthening regional capacity building in nuclear security; (2) establishing an ASEAN-Northeast Asia network of nuclear security centers of excellence (COEs) and knowledge centers; and (3) enhancing regional nuclear emergency preparedness and response. The article also explores the future of collaboration among International Nuclear Security Education Network (INSEN) members in the Asia-Pacific region, with Southeast Asian members as key drivers, to further strengthen regional nuclear security governance through sustainable nuclear security education.
Keywords: ASEAN; nuclear security; nuclear security education; INSEN; Centers of Excellence; nuclear governance